0002 Go to bed! A systematic review and meta-analysis of bedtime procrastination determinants and sleep outcomes. (25th May 2022) - Hill, Vanessa; Ferguson, Sally; Rebar, Amanda; Shriane, Alexandra; Vincent, Grace
Abstract: Introduction: Bedtime procrastination, the volitional delay of going to bed without any external circumstances causing the delay, is associated with poor sleep outcomes. Alleviating bedtime procrastination is an important target for interventions to promote adequate sleep, yet the social cognitive, biological, and behavioural determinants of bedtime procrastination are poorly understood. The present study aimed to conduct a systematic review, narrative synthesis, and meta-analysis of (1) the underlying determinants of bedtime procrastination, and (2) the strength and direction of the relationship between bedtime procrastination and sleep outcomes. Methods: A database search was conducted through CINAHL, EMBASE, PsychINFO, PubMed, Scopus and Web of Science, using keywords related to procrastination, delay, bedtime and sleep. Results: A total of 2087 records were identified, and 38 publications met the inclusion criteria. Random-effects meta-analysis for bedtime procrastination and sleep outcomes is ongoing. Preliminary findings suggest self-regulation, self-control and chronotype are the most prominent determinants. Conclusion: Future research should expand focus to identify a broader range of determinants. Given that there are multiple benefits to a theory-based approach to behaviour change interventions, further research exploring determinants will be able to guide the development of interventions targeting bedtime procrastination. Support (If Any) :